2015
DOI: 10.1177/1932296815581052
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia in Type 2 Diabetes - More Common Than You Think

Abstract: Background: Hypoglycemia is often the limiting factor for intensive glucose control in diabetes management, however its actual prevalence in type 2 diabetes (T2DM) is not well documented. Methodology: A total of 108 patients with T2DM wore a continuous glucose monitoring system (CGMS) for 5 days. Rates and patterns of hypoglycemia and glycemic variability (GV) were calculated. Patient and medication factors were correlated with rates, timing, and severity of hypoglycemia. Results: Of the patients, 49.1% had at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 38 publications
5
109
2
2
Order By: Relevance
“…This finding is similar with previous study showed that lower HbA1c level was associated with higher hypoglycemia prevalence. 10 This study found no association between the use of benzodiazepines, ACEI, RASB, CCB, beta-blockers, diuretics, and lipid lowering agents with hypoglycemic events during hospitalization. Although these drugs have been reported to increase the risk of hypoglycemic events, 9 it is likely that most hypoglycemic episodes are relatively mild or undocumented.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…This finding is similar with previous study showed that lower HbA1c level was associated with higher hypoglycemia prevalence. 10 This study found no association between the use of benzodiazepines, ACEI, RASB, CCB, beta-blockers, diuretics, and lipid lowering agents with hypoglycemic events during hospitalization. Although these drugs have been reported to increase the risk of hypoglycemic events, 9 it is likely that most hypoglycemic episodes are relatively mild or undocumented.…”
Section: Resultsmentioning
confidence: 75%
“…Research conducted in Atlanta found that the most hypoglycemic associated events were skipping meals or delaying meals. 10 A study conducted in Mexico in patients treated in the emergency room found that a history of fasting or skipping meals before admission increased the probability of occurrence hypoglycemic nearly 20 fold. 11 Previous studies also showed that restriction of carbohydrate intake was one of the drug-induced hypoglycemic risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…При оценке гипогликемий в стационаре на фоне инсулинотера-пии 6-кратное измерение гликемии в день позволило выя-вить гипогликемии у 22% пациентов при их частоте в 72% по результатам мониторирования в течение 2 суток [6]. В другом исследовании [10], включавшем 108 пациентов с сахарным диабетом 2-го типа с различной сахароснижа-ющей терапией, хотя бы один эпизод гипогликемии был выявлен у 49% пациентов и у 37% отмечались ночные гипо-гликемии. Также из всех эпизодов гипогликемии 75% были бессимптомными, что демонстрирует низкую надежность определения гипогликемий только лишь на основе симпто-мов или измерения глюкозы крови при их появлении.…”
Section: эндокринологияunclassified
“…59 Gehlaut et al found that 49% of patients with type 2 diabetes in their study had at least one episode of hypoglycemia during a 5-day analysis with CGM and many of those hypoglycemic episodes were asymptomatic. 58 They also found that 21% of those patients found to have hypoglycemia had values <50 mg/dL and episodes were most common in those on insulin. Cariou et al 57 evaluated a mixed population of patients with type 1 and 2 diabetes in an observational study over 30 days and found that 45% of patients reported at least one episode of hypoglycemia.…”
Section: Evidence For General Benefit Of Cgm In Type 2 Diabetesmentioning
confidence: 99%
“…The rate of hypoglycemia in type 2 diabetes is higher than usually appreciated. [57][58][59] For example Lipska et al reported that 10.8% of patients in the large database experienced severe hypoglycemia. 59 Gehlaut et al found that 49% of patients with type 2 diabetes in their study had at least one episode of hypoglycemia during a 5-day analysis with CGM and many of those hypoglycemic episodes were asymptomatic.…”
Section: Evidence For General Benefit Of Cgm In Type 2 Diabetesmentioning
confidence: 99%